Hollow Atomic Force Microscopy Cantilevers with Nanoscale Wall Thicknesses. Issue 51 (28th October 2021) - Cha, Wujoon; Campbell, Matthew F.; Hasz, Kathryn; Nicaise, Samuel M.; Lilley, Drew E.; Sato, Takaaki; Carpick, Robert W.; Bargatin, Igor
Abstract: In atomic force microscopy, the cantilever probe is a critical component whose properties determine the resolution and speed at which images with nanoscale resolution can be obtained. Traditional cantilevers, which have moderate resonant frequencies and high quality factors, have relatively long response times and low bandwidths. In addition, cantilevers can be easily damaged by excessive deformation, and tips can be damaged by wear, requiring them to be replaced frequently. To address these issues, new cantilever probes that have hollow cross‐sections and walls of nanoscale thicknesses made of alumina deposited by atomic layer deposition are introduced. It is demonstrated that the probes exhibit spring constants up to ≈100 times lower and bandwidths up to ≈50 times higher in air than their typical solid counterparts, allowing them to react to topography changes more quickly. Moreover, it is shown that the enhanced robustness of the hollow cantilevers enables them to withstand large bending displacements more readily and to be more resistant to tip wear. Abstract : This article presents hollow alumina thin‐walled atomic force microscopy cantilevers that scan specimens rapidly yet wear down more slowly than their solid silicon counterparts. With wall thicknesses as low as 20 nm, these improvements are attributable to the probes′ robust thin‐walled hollow atomic‐layer‐deposited alumina profiles, which increase their bandwidth in air and provide impact resilience and wear resistance.